The formation of secondary linguistic identity in the process of future pharmacists’ individual work - Agnessa Tomashevs’ka (ScienceRise: Pedagogical Education, 2017)
Considered in the article are the language identity formation parameters of professionally-directed teaching as the key approach to didactic potential autonomy pharmacists’ learning; the conceptual sphere of the notion secondary linguistic ego determination is specified; special attention on exploring the contemporary basic theories of the ESL researchers concerning the most productive a learner-centered technology is focused; the development and implementation rationality of the partial functional model incorporated the lexical, contextual and procedural components aimed at obtaining knowledge through individualization, improving skills, enhancing creative nature aptitudes is substantiated; the cognitive duomodular program in terms of the interrelated dominant format of individual work within and outside the auditorium through the complex of the traditional and interactive forms training for approximating teaching to real professionally-oriented situations of pharmaceutical practice involving three main parts: Searching for Information, Reading and Context-based Talk Experience, Formative – Summative Evaluation Tests included meaningful material drilling is suggested; it is analyzed the possibility of the educational guide arrangement due to the ways of raising students’ intercultural competence as principal target to guarantee effective communication with other environment speakers to ensure students’ ability for their own action style choice in the professional English mastering are emphasized